2002
DOI: 10.1002/dev.10049
|View full text |Cite
|
Sign up to set email alerts
|

Intersensory redundancy facilitates discrimination of tempo in 3‐month‐old infants

Abstract: L. Bahrick and R. Lickliter (2000) proposed an intersensory redundancy hypothesis that states that information presented redundantly and in temporal synchrony across two or more sensory modalities selectively recruits infant attention and facilitates perceptual learning more effectively than does the same information presented unimodally. In support of this view, they found that 5-month-old infants were able to differentiate between two complex rhythms when they were presented bimodally, but not unimodally. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
172
2
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 173 publications
(192 citation statements)
references
References 59 publications
13
172
2
5
Order By: Relevance
“…Likewise, no age-related change was detected for looking at the eyes in any condition. Th ese results are inconsistent with the intersensory redundancy hypothesis (Bahrick, Flom, & Lickliter, 2002;Lewkowicz, 2000), which would predict increased att ention to the mouth only for congruent (redundant) speech cues. Some methodological diff erences between the Tomalski et al (2013) study and the Lewkowicz and Hansen-Tift (2012) study may have contributed to these inconsistencies.…”
Section: Av Mismatch Detection As a Test Of The Intersensory Redundancontrasting
confidence: 57%
“…Likewise, no age-related change was detected for looking at the eyes in any condition. Th ese results are inconsistent with the intersensory redundancy hypothesis (Bahrick, Flom, & Lickliter, 2002;Lewkowicz, 2000), which would predict increased att ention to the mouth only for congruent (redundant) speech cues. Some methodological diff erences between the Tomalski et al (2013) study and the Lewkowicz and Hansen-Tift (2012) study may have contributed to these inconsistencies.…”
Section: Av Mismatch Detection As a Test Of The Intersensory Redundancontrasting
confidence: 57%
“…For example, five-month-old infants habituated to a multisensory rhythm can discriminate a novel rhythm, while infants habituated to a unisensory rhythm fail (Bahrick and Lickliter, 2000). Similarly, three-month-old infants can differentiate between variants of tempo following bimodal but not unimodal habituation (Bahrick, Flom, and Lickliter, 2002). This precision also increases with age: Infants at six months successfully discriminate a 1:2 ratio but not a 2:3 ratio change in the duration of a multisensory audiovisual event, whereas by ten months infants successfully discriminate a 2:3 ratio (vanMarle and Wynn, 2006;Brannon, Suanda & Libertus, in press).…”
Section: Discussionmentioning
confidence: 99%
“…Five-month-old infants habituated to a multisensory rhythm were shown to discriminate a novel rhythm, while infants habituated to a unisensory rhythm were unable to do so (Bahrick and Lickliter, 2000). Similarly, three-month-old infants can differentiate between variants of tempo following bimodal but not unimodal habituation (Bahrick, Flom, and Lickliter, 2002). Intersensory redundancy in the form of synchronized vocalizations and object motion facilitated learning of arbitrary speechobject relations in seven-month-old infants (Gogate and Bahrick, 1998).…”
Section: Introductionmentioning
confidence: 95%
“…Some of the initial experiments investigating the intersensory redundancy hypothesis examined infants' (i.e., 3-to 5-montholds') discrimination of different amodal properties such as rhythm and tempo within unisensory or unimodal contexts as well as multimodal or multisensory contexts (Bahrick & Lickliter, 2000;Bahrick, Flom, & Lickliter, 2002). For example, Bahrick and Lickliter (2000) showed that 5-month-olds discriminate a change in the rhythm of a plastic toy hammer hitting a surface when provided redundant and temporally synchronous bimodal auditory-visual stimulation, but fail to discriminate a change in the event's rhythm when provided unimodal auditory, unimodal visual Intersensory Perception 9 stimulation, or temporally asynchronous bimodal stimulation (Bahrick & Lickliter, 2000).…”
Section: Evidence Supporting the Predictions Of The Intersensory Redumentioning
confidence: 99%